Sincerely, Harriet - Searle, Sarah Winifred (Graphic Universe, 2019)
In 1996 Chicago, thirteen-year-old Harriet Flores, living with boredom, loneliness, and a chronic illness, lets her imagination run wild--with mixed results--and learns about the power of storytelling.